Functionalized manganese iron oxide nanoparticles: a dual potential magneto-chemotherapeutic cargo in a 3D breast cancer model - Phalake, Satish S; Somvanshi, Sandeep B; Tofail, Syed A. M; Thorat, Nanasaheb D; Khot, Vishwajeet M (Nanoscale, 2023)
Localized heat generation from manganese iron oxide nanoparticles (MIONPs) conjugated with chemotherapeutics under the exposure of an alternating magnetic field (magneto-chemotherapy) can revolutionize targeted breast cancer therapy. On the other hand, the lack of precise control of local temperature and adequate MIONP distribution in laboratory settings using the conventional two-dimensional (2D) cellular models has limited its further translation in tumor sites. Our current study explored advanced 3D in vitro tumor models as a promising alternative to replicate the complete range of tumor characteristics. Specifically, we have focused on investigating the effectiveness of MIONP-based magneto-chemotherapy (MCT) as an anticancer treatment in a 3D breast cancer model. To achieve this, chitosan-coated MIONPs (CS-MIONPs) are synthesized and functionalized with an anticancer drug (doxorubicin) and a tumor-targeting aptamer (AS1411). CS-MIONPs with a crystallite size of 16.88 nm and a specific absorption rate (SAR) of 181.48 W g −1 are reported. In vitro assessment of MCF-7 breast cancer cell lines in 2D and 3D cell cultures demonstrated anticancer activity. In the 2D and 3D cancer models, the MIONP-mediated MCT reduced cancer cell viability to about 71.48% and 92.2%, respectively. On the other hand, MIONP-mediated MCT under an AC magnetic field diminished spheroids' viability to 83.76 ± 2%, being the most promising therapeutic modality against breast cancer. Dual magneto-chemotherapeutic effects on a 3D breast cancer model after 10, 20 and 30 min of treatment.